The Effect of Conscientiousness, Communication Satisfaction and Job Characteristics on Employee Performance - Nurul Azis; Prayekti Prayekti; Jajuk Herawati (Jurnal Ilmu Manajemen Profitability, 2023)
This study aims to determine the effect of Conscientiousness, Communication Satisfaction and Job Characteristic variables on employee performance. This research was conducted at KUD Sadar Sejahtera Musi Rawas. The sample of this research used total sampling so that the respondents in this study were 67 respondents. The test instrument used in this research is the Test of Validity and Reliability, Test of Classical Assumptions. The data analysis technique used in this study is multiple linear regression analysis. The results of this study show that Conscientiousness, Communication Satisfaction and Job Characteristics affect employee performance